1997
DOI: 10.2355/isijinternational.37.1129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ti-S-C-containing Multi-phase Precipitates in Ultra-low Carbon Steels by Analytical Electron Microscopy.

Abstract: Pittsburgh, Belgium,The Ti-. S-, and C-containing particles in ultra-Iow carbon (ULC) interstitial free steels are frequently multi-phase in nature, consisting of TiS (9R) and Ti4C2S2 (H)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…TiC has a fcc crystal structure (space group: Fm3m) with lattice parameters aϭ4.2-4.4 Å. 4) Thermodynamically TiC is formed in the ferrite phase stability range (ϳ700-900°C), mostly as dispersed particles. In the experimental steels fine TiC precipitates are observed throughout the matrix after annealing, however, their volume fraction, size and distribution vary from steel to steel.…”
Section: Ticmentioning
confidence: 99%
See 1 more Smart Citation
“…TiC has a fcc crystal structure (space group: Fm3m) with lattice parameters aϭ4.2-4.4 Å. 4) Thermodynamically TiC is formed in the ferrite phase stability range (ϳ700-900°C), mostly as dispersed particles. In the experimental steels fine TiC precipitates are observed throughout the matrix after annealing, however, their volume fraction, size and distribution vary from steel to steel.…”
Section: Ticmentioning
confidence: 99%
“…Researchers, especially DeArdo and his group, [4][5][6][7][8] have extensively studied and reported the precipitation behavior of IF steels. However, there is no systematic report till date on the nature and extent of precipitation in IFHS steels.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely accepted that TiS is predominantly formed at temperatures higher than Ti 4 C 2 S 2 . [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][68][69][70][71][72][73][74] In addition, (d) solubility products of TiS and Ti 4 C 2 S 2 in austenite region have been proposed by many groups. 31,35,37,44,52,53,62,68) It has often been stated that sulfide precipitation in austenite phase can be fully described through thermodynamical calculation, but all the calculations are not always consistent with each other.…”
Section: Purpose Of Our Studies and Reviews Of Past Reportsmentioning
confidence: 99%
“…In experimental steel, TiC is finer and has a denser distribution than TiN and Ti 4 C 2 S 2 . The EDS spectrum of the particle in Figure 4b shows that the atomic ratio of Ti to S is close to 2 (as shown in Figure 4e), and the particle can be identified as Ti 4 C 2 S 2 [9]. The distribution of Ti 4 C 2 S 2 is very inhomogeneous, often in the shape of strings or clusters (as shown in Figure 4b).…”
Section: Microstructurementioning
confidence: 93%
“…There are several factors which affect the precipitation behavior of titanium precipitates, i.e., chemical composition, finishing temperature, coiling temperature, annealing temperature and so on. It is reported that Ti and S content will affect the type and fraction of precipitates [9]. Mo can also influence the precipitation behavior of TiC particles [10].…”
Section: Methodsmentioning
confidence: 99%